The ‘Gift Exchange’: a metaphor for understanding the relationship between educator commitment and student effort on placement - Clouder, Lynn; Adefila, Arinola (International Journal of Practice-based Learning in Health and Social Care, 2016)
‘It is only with the heart that one can see rightly; what is essential is invisible to the eye’ Antoine de Saint Exupery (1900–1944) It is a truism that a sound working relationship between student and practice educator is a major contributory factor to positive placement experiences for health and social care students. However, there is limited research that goes any further in explaining how this relationship is established and might work. This paper utilizes the metaphor of the ‘gift’ to emphasize the importance of generosity and reciprocity within the student/practice educator relationship. Qualitative research findings, generated from interviews with practice educators, reveal that whilst the educator gives the student the benefit of their expertise and provides access to opportunities to learn from practice, the student is expected to return this ‘investment’ by demonstrating that they too are putting in effort, for instance, by showing keenness to learn, and developing subject knowledge and skills. Although educators demonstrate a sense of obligation or duty to support students in their endeavours this commitment is not necessarily unconditional; reciprocal student effort is an important motivator for some practice educators for whom a demonstrable response to their input confirms their own sense of identity as educators and clinicians.